International Faculty Member Sociocultural Adjustment And Intention To Stay: Evidence From North Cyprus - Tanova, Cem; Ajayi, Olusegun (Asian Academy of Management (AAM), 2016)
This study examines how sociocultural adjustment of international faculty members working in universities in North Cyprus may relate to their intention to stay. The antecedents of sociocultural adjustment are also investigated. The study used a questionnaire administered to a sample of 85 international faculty members working at five universities in North Cyprus in order to investigate the factors that influence their cultural adjustment in terms of work, interaction and general adjustment. The study also investigates how the facets of socio cultural adjustment may influence a faculty member's intention to stay in their current institution. Data analysis and hypothesis testing was carried out using a path analysis in SPSS AMOS 20. Previous international work experiences were found to influence and facilitate all facets of cultural adjustment. Perceived cultural similarity was linked to work and interaction adjustment. The strongest predictor of intention to remain in the current country and institution was interaction adjustment. General and work adjustment's influence on intention to stay is mediated by interaction adjustment. The results indicate that academic institutions that rely on international academics need to develop effective selection systems. The selection and recruitment systems should not only focus on technical skills but also on the characteristics and experiences that will facilitate adjustment to a new culture. Academic institutions should also ensure that orientation and mentoring programs are provided that facilitate adjustment not only to the organisation but also to the culture.